The Effectiveness of Family 100 Game in Mastering Mufradat in Arabic Language Learning - Erwani, Erwani; Nurhidayati, Nurhidayati; Furqan, Muhammad Rizalul (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2025)
This study aims to describe the implementation of the Family 100 game in Arabic language learning, specifically in mastering vocabulary and examine the effectiveness of using the Family 100 Game in enhancing Arabic vocabulary mastery (mufradat) in class XI IPA 2 at SMA Islam Singosari. Given the importance of vocabulary mastery in Arabic language learning, this research is expected to contribute to improving the quality of learning. A quantitative approach with a Pre-Experimental design was applied in this study, using the One Group Pre-test and Post-test Design model. The sample consisted of 30 students from class XI IPA 2, and data were collected through pre-test and post-test assessments, as well as documentation. Data analysis was conducted using normality tests, homogeneity tests, the Wilcoxon test, and the N-Gain test to measure the effectiveness of the game-based learning method. The results showed that the implementation of the Family 100 Game significantly improved Arabic vocabulary mastery. This was evident from the significant increase in pre-test and post-test scores, with an N-Gain value of .8268 and N-persen 82.6825. The Wilcoxon test produced a significant value of 0.000, indicating a significant difference between the pre-test and post-test results.